Bank Indonesia Law Relations With The Financial Services Authority (FSA) in Indonesian Banking Supervision - Zulfi Diane Zaini (International Conference On Law, Business and Governance (ICon-LBG), 2013)
With the presence of FSA, the supervision function of financial institutions, banks and nonbanks,will be taken over by FSA. Meanwhile Bank Indonesia as the Central Bank only acts as a regulatorto keep monetary policy for monetary stability. The formation of FSA will thus have an impact tochanges on four laws and regulations related to insurance, capital markets, banking, as well as the CapitalMarket Supervisory Agency and other financial institutions. Substantially the presence of FSA mustbridge the importance of each monitoring regulator at this moment.The duty of FSA in accordance with Article 6 of Law Number 21 Year 2011 regarding FSA ie:To carry out regulation and supervision of financial services activity in the banking sector, activities offinancial services in the Capital Market, activity in the financial services in insurance sector, pensions,funding agencies and other financial services institutions.Institutionally, FSA is outside the Government which means that FSA is not part of thegovernment authority. However there is a possibility of government representation elements existencebecause in reality FSA is the authority in the financial services sector that has strong relationships andlinkages with other authorities, in this case the fiscal authority (Minister of Finance) and the monetaryauthority (Bank Indonesia).The provision of Article 69 paragraph (1) letter (a) of Law no. 21 year 2011 asserts that the taskof Bank Indonesia in regulating and overseeing banks that are moved to FSA is a job of arrangements andsupervision related with microprudential, while Bank Indonesia still has a job related to macroprudentialbanking arrangements. Associated with it, the task of banking regulation is not fully implementedindependently by FSA because microprudential and macroprudential regulation would be highlyrelevant. Thus it can be seen that FSA still has a "special relationship" with Bank Indonesia, especially inbanking regulation and supervision .